Suitability of Cell-Based Label-Free Detection for Cytotoxicity Screening of Carbon Nanotubes. (27th November 2013) - Meindl, Claudia; Absenger, Markus; Roblegg, Eva; Fröhlich, Eleonore
Abstract : Cytotoxicity testing of nanoparticles (NPs) by conventional screening assays is often complicated by interference. Carbon nanotubes (CNTs) are particularly difficult to assess. To test the suitability of cell-based label-free techniques for this application, a panel of CNTs with different diameters and surface functionalizations was assessed by impedance-based technique ( xCELLigence RTCA) and automated microscopy (Cell-IQ) compared to formazan bioreduction (MTS assay). For validation of the label-free systems different concentrations of ethanol and of amine (AMI) polystyrene NPs were used. CNTs were evaluated in various cell lines, but only endothelial EAhy926 cells and L929 and V79 fibroblasts could be evaluated in all systems. Polystyrene particles obtained similar results in all assays. All systems identified thin (<8 nm) CNTs as more cytotoxic than thick (>20 nm) CNTs, but detection by xCELLigence system was less sensitive to CNT-induced cytotoxicity. Despite advantages, such as continuous monitoring and more detailed analysis of cytotoxic effects, label-free techniques cannot be generally recommended for cytotoxicity screening of NPs.